The Effectiveness of Health Management-Assisted Technology on Glycated Hemoglobin Levels in Patients with Type 2 Diabetes Mellitus: Meta-Analysis - Fajar Novianto; Atika Mima Amalin; Anggun Fitri Handayani; Anggraini Ambarsari; Diana Ode; Alfi Makrifatul Azizah; Ayu Trisni Pamilih; Annisa Fitriana Damalita; Fathiyyatu Assa'diy Firda; Ahmad Syauqi Mubarok (Journal of Health Policy and Management, 2021)
Background: Given the number of patients failing to achieve control of Diabetes Mellitus (DM), it causes an increase in the incidence of DM complications. Along with the rapid development of technology in this era, this study aimed to prove the effectiveness of technology-based health management compared to usual treatment for levels glycated hemoglobin (HbA1c) in type 2 diabetes mellitus patients.Subjects and Method: This was a meta-analysis using a randomized controlled trial. Articles were obtained from PubMed, Google Scholar, and ResearchGate databases. The articles used in this study were those published from 2012-2021. The search article was carried out by considering the eligibility of the criteria determined using the PICO model. Population: type 2 DM patients (HbA1c>7%), Intervention: health management-assisted technology, Comparison: usual care Outcome: HbA1c levels. There were 10 articles used with a sample size of 1693 people who were divided into two groups (845 people in the health management-assisted technology group and 848 people in the group usual care). Articles were analyzed using Review Manager 5.3 Application to determine the Standard Mean Difference (SMD) and heterogeneity of the study sample.Results: From 10 articles that were processed using RevMan 5.3, significant results were obtained, this is indicated by the overall effect (diamond) which does not touch the vertical line H0 (d= 0) and can also be seen from the 95% CI range of -0.62 to -0.13 which shows significant because it does not pass the number 0 (SMD= -0.37; 95% CI= -0.62 to -0.13; p= 0.003). The heterogeneity of the research data shows I2 = 82% so that the distribution of the data is very heterogeneous (random effects model).Conclusion: Using technology to help health management of patients with type 2 diabetes mellitus can reduce HbA1c levels compared to usual care.Keywords: Health management, technology, diabetes mellitus, HbA1cCorrespondence: Fajar Novianto. Center for Research and Development of Medicinal Plants and Traditional Medicine, National Institute of Health of Health, Jl. Raya Lawu No. 11 Karanganyar, Central Java. Email: dr.fajarnovianto@gmail.com.Journal of Health Policy and Management (2021), 06(02): 81-93https://doi.org/10.26911/thejhpm.2021.06.02.01